1
$\begingroup$

So recently I've been studying Discrete Mathematics using a book written by Susanna S. There's an exercise in which she asks whether $(p ⊕ q) \wedge r = (p \wedge r) ⊕ (q \wedge r)$ I've done it using a truth table and concluded that both sides are logically equivalent, by checking each entry, but I couldn't do it using laws of boolean algebra. I've just got stuck trying to manage one expression into the other

$\endgroup$
3
$\begingroup$

\begin{align} (p\land r)\oplus (q\land r)&=\big((p\land r)\land\lnot(q\land r)\big)\lor\big(\lnot(p\land r)\land(q\land r)\big)&\text{Definition of }\oplus\\ &=\big((p\land r)\land(\lnot q\lor \lnot r)\big)\lor\big((\lnot p\lor \lnot r)\land(q\land r)\big)&\text{De-Morgans}\\ &=(p\land r\land\lnot q)\lor(p\land r\land\lnot r)\lor(q\land r\land\lnot p)\lor(q\land r\land\lnot r)&\text{Distribute}\\ &=(p\land r\land\lnot q)\lor(q\land r\land\lnot p)&\text{Simplify}\\ &=\big((p\land\lnot q)\lor(q\land\lnot p)\big)\land r&\text{Factor out}\\ &=(p\oplus q)\land r&\text{Definition of }\oplus \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.